Perbandingan Efek antara Core Stability Exercise dengan Pilates Exercise terhadap Peningkatan Fleksibilitas Lumbal Mahasiswa dengan Overweight di Makassar, Indonesia - Armita Iswardani Irawan; Nurhikmawaty Nurhikmawaty; Irianto Irianto (Faculty of Medicine, Hasanuddin University., 2020)
Overweight is a problem that can reduce a person's flexibility. Excessive body weight will certainly give great compression to the spinal padding so that there is a risk of changes in posture and lower back injuries. Increased BMI such as overweight can reduce the flexibility of the body, especially lumbar flexibility, because the lumbar is the lowest part of the spine which gets the most pressure and is a cushion of body weight and body movements. Physical activity such as core stability exercise and pilates can help provide changes in increasing lumbar flexibility. This study used the pre-experimental design method with two group pretest - posttest design. 30 overweight students at Faculty of Nursing Hasanuddin University were divided into core groups and pilates groups. Samples were given 12 treatments and measured using Modified Schober Test (MST). We observed changes before and after giving core stability exercise and pilates exercise. When comparing core stability exercise and pilates exercise pilates is more effective than core stability exercise